2022
DOI: 10.1038/s41598-022-14769-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial endophytes as indicators of susceptibility to Cercospora Leaf Spot (CLS) disease in Beta vulgaris L.

Abstract: The fungus Cercospora beticola causes Cercospora Leaf Spot (CLS) of sugar beet (Beta vulgaris L.). Despite the global importance of this disease, durable resistance to CLS has still not been obtained. Therefore, the breeding of tolerant hybrids is a major goal for the sugar beet sector. Although recent studies have suggested that the leaf microbiome composition can offer useful predictors to assist plant breeders, this is an untapped resource in sugar beet breeding efforts. Using Ion GeneStudio S5 technology t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Results showed that most plant-beneficial bacteria detected on various plant-based media could not be detected by metabarcoding. The microbiome of the sugar beet has previously been analyzed using metabarcoding from various aspects: seasonal shifts in the lateral root microbiome [ 6 ], spatiotemporal changes in endophytic bacterial diversity [ 34 ], the rhizobiome of the sugar beet under different fertilizer systems [ 35 ], the leaf bacteriome in relation to the susceptibility of the sugar beet to beet curly top virus [ 36 ], and Cercospora leaf spot disease [ 37 ]. In this study, the microbiome of the sugar beet was investigated in two plant parts, the root and the leaf, and compared in different plant development stages (May, July, and October).…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that most plant-beneficial bacteria detected on various plant-based media could not be detected by metabarcoding. The microbiome of the sugar beet has previously been analyzed using metabarcoding from various aspects: seasonal shifts in the lateral root microbiome [ 6 ], spatiotemporal changes in endophytic bacterial diversity [ 34 ], the rhizobiome of the sugar beet under different fertilizer systems [ 35 ], the leaf bacteriome in relation to the susceptibility of the sugar beet to beet curly top virus [ 36 ], and Cercospora leaf spot disease [ 37 ]. In this study, the microbiome of the sugar beet was investigated in two plant parts, the root and the leaf, and compared in different plant development stages (May, July, and October).…”
Section: Discussionmentioning
confidence: 99%
“…With currently available data, it appears that phyllosphere bacterial diversity shifted and increased during domestication, while rhizosphere diversity decreased (see Section 2.6); sea beet phyllospheres are strongly dominated by Sphingomonas and Methylobacterium , together accounting for ca. 84% relative abundance (Broccanello et al, 2022 ). This however could as well refer to fertilization regimes, since bacterial phyllosphere microbiomes in sugar beet respond stronger upon NPK fertilization than in bacterial endosphere communities (Okazaki et al, 2021 ).…”
Section: Part I: Microbial Journeys On and In Sugar Beets: From Seed ...mentioning
confidence: 99%
“…Bacterial phyllosphere communities differ between petioles and laminae: Phyllobacterium, Methylobacterium , and Sphingomonas are higher-abundant, while Pseudomonas and Enterobacteriaceae are lower-abundant in petioles (Okazaki et al, 2021 ). Phyllosphere abundance of Methylobacterium and Mucilaginibacter was further linked to tolerance toward leaf pathogen Cercospora beticola in both sea beets and sugar beets (Broccanello et al, 2022 ). In contrast to bacteria, fungi isolated from sugar beet leaves usually belong to opportunistic plant pathogens ( Alternaria, Aspergillus, Cladosporium, Acremonium, Fusarium, Penicillium, Phoma, Plectosphaerella, Pleospora, Pythium ) but also saprobionts ( Cryptococcus, Epicoccum, Sporobolomyces, Stemphylium ) (Thompson et al, 1993 ; Larran et al, 2000 ; Shi et al, 2009a ; Pusenkova et al, 2016 ).…”
Section: Part I: Microbial Journeys On and In Sugar Beets: From Seed ...mentioning
confidence: 99%
“… 54 Meanwhile, the abundance of bacterial endophytes such as Methylobacterium and Mucilaginibacter can be correlated with increased sensitivity to CLS disease. 55 These biomarkers could be employed as indicators for breeding resistant varieties of sugar beet. Compared with the analysis of differential proteins expression, metabolites profile is a more convenient method in practice.…”
Section: Disease Managementmentioning
confidence: 99%